Justification of rational constructive and technological solutions for panel housing construction with the application of engineering approaches - Belbaeva A.A., Бельбаева А.А. (Рroblems of engineering and professional education, 2022)
The article examined the possibilities of developing technologies for panel housing construction. Large-panel housing construction spread to the territory of Kazakhstan in the second half of the 50s and is still relevant. The purpose of this article is to review and analyze the achievements in the field of panel construction. Analyzed indicators of housing construction and construction of social facilities.